Controls on the formation of stratabound dolostone bodies, Hammam Faraun Fault block, Gulf of Suez. Issue 6 (31st March 2018) - Hirani, Jesal; Bastesen, Eivind; Boyce, Adrian; Corlett, Hilary; Gawthorpe, Rob; Hollis, Cathy; John, Cédric M.; Robertson, Hamish; Rotevatn, Atle; Whitaker, Fiona
Abstract: Dolomitization is commonly associated with crustal‐scale faults, but tectonic rejuvenation, diagenetic overprinting and a fluid and Mg mass‐imbalance often makes it difficult to determine the dolomitization mechanism. This study considers differential dolomitization of the Eocene Thebes Formation on the Hammam Faraun Fault block, Gulf of Suez, which has undergone a simple history of burial and exhumation as a result of rifting. Stratabound dolostone bodies occur selectively within remobilized sediments (debrites and turbidites) in the lower Thebes Formation and extend into the footwall of, and for up to 2 km away from, the Hammam Faraun Fault. They are offset by the north–south trending Gebel fault, which was active during the earliest phases of rifting, suggesting that dolomitization occurred between rift initiation (26 Ma) and rift climax (15 Ma). Geochemical data suggest that dolomitization occurred from evaporated ( ca 1·43 concentration) seawater at less than ca 80°C. Geothermal convection is interpreted to have occurred as seawater was drawn down surface‐breaching faults into the Nubian sandstone aquifer, convected and discharged into the lower Thebes Formation via the Hammam Faraun Fault. Assuming a ca 10 Myr window for dolomitization, a horizontal velocity of ca 0·7 m year −1 into the Thebes Formation is calculated, with fluid flux and reactivity likely to have been facilitated by fracturing. Although fluids were at least marginally hydrothermal, stratabound dolostone bodies do not contain saddle dolomite and there is no evidence of hydrobrecciation. This highlights how misleading dolostone textures can be as a proxy for the genesis and spatial distribution of such bodies in the subsurface. Overall, this study provides an excellent example of how fluid flux may occur during the earliest phases of rifting, and the importance of crustal‐scale faults on fluid flow from the onset of their growth. Furthermore, this article presents a mechanism for dolomitization from seawater that has none of the inherent mass balance problems of classical, conceptual models of hydrothermal dolomitization.